Perception of and satisfaction with the clinical learning environment among nursing students. (June 2015) - D'Souza, Melba Sheila; Karkada, Subrahmanya Nairy; Parahoo, Kader; Venkatesaperumal, Ramesh
Summary: Background: Clinical nursing education provides baccalaureate nursing students an opportunity to combine cognitive, psychomotor, and affective skills in the Middle East. Objective: The aim of the paper is to assess the satisfaction with and effectiveness of the clinical learning environment among nursing students in Oman. Design: A cross-sectional descriptive design was used. Setting and Participants: A convenience sample consisting of 310 undergraduate nursing students was selected in a public school of nursing in Oman. Methods: Ethical approval was obtained from the Research and Ethics Committee, College of Nursing in 2011. A standardized, structured, validated and reliable Clinical Learning Environment Supervision Teacher Evaluation instrument was used. Informed consent was obtained from all the students. Data was analyzed with ANOVA and structural equation modeling. Results: Satisfaction with the clinical learning environment (CLE) sub-dimensions was highly significant and had a positive relationship with the total clinical learning environment. In the path model 35% of its total variance of satisfaction with CLE is accounted by leadership style, clinical nurse commitment (variance = 28%), and patient relationships (R 2  = 27%). Higher age, GPA and completion of a number of clinical courses were significant in the satisfaction with the CLE among these students. Conclusions: Nurse educators can improvise clinical learning placements focusing on leadership style, premises of learning and nursing care, nurse teacher, and supervision while integrating student, teacher and environmental factors. Hence the clinical learning environment is integral to students' learning and valuable in providing educational experiences. Relevance to Practice: The CLE model provides information to nurse educators regarding best clinical practices for improving the CLE for BSN students.